The Role of Government Investment and Policy to Overcome Poverty in Indonesia - Bado Riyono; Sumaryoto; Meirinaldi (MultiTech Publisher, 2023)
The role of government policy in overcoming poverty sometimes has major implications for the economy. Likewise with investments that require attractive packages for foreign and domestic investors. This study aims to explain the importance of investment and government policies in overcoming poverty. The method used is the method of literature review. Data were taken from various books, journals and data from the central statistics bureau. Government policy and investment are supporting factors that can determine the decision making to overcome poverty. The government can provide investment convenience to investors in order to increase employment opportunities for the community. In addition, infrastructure development is one of the main focuses as the foundation for development which will continue to be improved, especially related to the main link to productive economic centers.